ANALISIS STANDAR PROSES PENDIDIKAN MENUJU PENDIDIKAN YANG BERKUALITAS - Munawir Munawir; Narwi Subandi (PGSD Universitas Muhammadiyah Cirebon, 2022)
The learning process becomes effective if it is accompanied by a system that supports educational progress. This study uses a literature study method that relies on bibliographic sources from books and articles in scientific journals related to the subject matter. The results of this study indicate that: 1) The standard of the educational process is the national standard of education, which means the standard of the educational process in question applies to every formal educational institution at a certain level of education wherever the educational institution is located nationally. 2) The standard process is related to the implementation of learning, which means that the standard of the educational process contains about how learning should take place. 3) The standard of the educational process is directed at achieving graduate competency standards. Thus, graduate competency standards are the main source or reference in determining the standard of the educational process. Keywords: Process Standards, Quality, Learning. process standards are criteria regarding the implementation of learning in an educational unit to achieve Graduate Competency Standards. Keywords: Analysis of Educational Process Standards